Chicken Pox Associated Bilateral Retinal Vasculitis in an Immunocompetent Young Male; an Unusual Case Report - Gurung, Rajya Laxmi (Birat Journal of Health Sciences, 2019)
Chicken pox is considered as benign infectious disease with variable ocular manifestations. We report a case of bilateral retinal vasculitis following chicken pox in a healthy 17-year-old male. The retinal manifestation is stabilized by treatment with oral acyclovir in combination with systemic steroids.